LITERARY CONTEXT OF INTERWAR SERBIAN CHORAL MUSIC COMPOSED TO VERSES OF ARTISTIC POETRY - Tasić, Nataša D (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
Choral music in Serbia between two world wars developed simultaneously in the genre fields of spiritual and folklore music, and music written to the verse of artistic poetry. Literary context of the latter genre mostly involved poetry from the period of romanticism. Apart from that, certain authors gladly wrote music to the lyric poetry of their contemporaries, and there are also examples in which composers reached out to the poetry from distant past. This paper deals with the analysis of representation of verses of certain poets in the work of musical artists. The reasons for the domination of certain thematic fields and influence of stylistic orientation of lyricists to composer’s choices are some of the most significant conclusions of this text.